Integrated metabolite profiling and transcriptome analysis identify candidate genes involved in diterpenoid alkaloid biosynthesis in Aconitum pendulum - Wang, Ting; Xu, Guoqing; Liu, Zhaoyu; Ding, Xiaoxia; Wang, Liangting; Leng, Liang; Wang, Can; Xu, Tong; Zhang, Yi (Frontiers in Plant Science, 2025)
IntroductionAconitum pendulum is a well-known Tibetan medicine that possesses abundant diterpenoid alkaloids (DAs) with high medicinal value. However, due to the complicated structures of DAs and the associated challenges in vitro synthesis presents, plants like Aconitum pendulum remain the primary source for DAs.MethodsGiven the underutilization of the A. pendulum, a thorough metabolomic and transcriptomic analysis was conducted on its flowers, leaves, and stems to elucidate the regulatory network underlying DA biosynthesis.ResultsMetabolomic profiling (utilizing UPLC-QQQ-MS/MS) identified 198 alkaloids, of which 61 were DAs and the relative abundance of DAs was different among different tissues. Without a reference genome, we performed de novo assembly of the transcriptome of A. pendulum. We generated 181,422 unigenes, among which 411 candidate enzyme genes related to the DA synthesis pathway were identified, including 34 differentially expressed genes (DEGs). Through joint analysis of transcriptome and metabolome data, we found a correlation between the detected metabolite levels in various tissues and the expression of related genes. Specifically, it was found that ApCYP1, ApCYP72, and ApCYP256 may be related to turupellin accumulation, while ApBAHD9, ApBAHD10, ApBAHD12 positively associated with the accumulation of aconitine. Furthermore, our study also revealed that genes involved in the diterpene skeleton synthesis pathway tend to be highly expressed in flowers, whereas genes related to DA skeleton synthesis and their subsequent modifications are more likely to be highly expressed in leaf and stem tissues. Functional analysis of gene families identified 77 BAHD acyltransferases, 12 O-methyltransferases, and 270 CYP450 enzyme genes potentially involved in the biosynthesis of DAs. The co-expression network between metabolites and related genes revealed 116 significant correlations involving 30 DAs and 58 enzyme genes.DiscussionThis study provides valuable resources for in-depth research on the secondary metabolism of A. pendulum, not only deepening our understanding of the regulatory mechanisms of DA biosynthesis but also providing valuable genetic resources for subsequent genetic improvement and metabolic engineering strategies.